2015
DOI: 10.1007/s10067-015-2910-5
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of methotrexate self-injection education videos on YouTube

Abstract: The aim of this study is to identify and evaluate the quality of videos for patients available on YouTube for learning to self-administer subcutaneous methotrexate. Using the search term "Methotrexate injection," two clinical reviewers analyzed the first 60 videos on YouTube. Source and search rank of video, audience interaction, video duration, and time since video was uploaded on YouTube were recorded. Videos were classified as useful, misleading, or a personal patient view. Videos were rated for reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
79
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 13 publications
9
79
1
7
Order By: Relevance
“…Singh et al and Rittenberg et al used a modified five-point DISCERN tool to assess rheumatoid arthritis and methotrexate injection videos on YouTube 23 24. Originally developed by Charnock and colleagues, the DISCERN tool enables evaluation of written health information 25.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al and Rittenberg et al used a modified five-point DISCERN tool to assess rheumatoid arthritis and methotrexate injection videos on YouTube 23 24. Originally developed by Charnock and colleagues, the DISCERN tool enables evaluation of written health information 25.…”
Section: Methodsmentioning
confidence: 99%
“…We also rated the quality of each video using the global quality scale. Bernard and colleagues originally published this scale and it has been used subsequently in other literature evaluating medical information on YouTube 23 24 26 27…”
Section: Methodsmentioning
confidence: 99%
“…In brief, we searched YouTube TM (www.youtube.com) in June 2019 using German melanoma-related keywords and included the first three pages of results. 5,6 Eligible videos had to contain information referring to cutaneous melanoma, be accessible for free and be provided in German. Videos were excluded if they were commercials, about melanoma in animals, without sound, music videos, cartoons or if the duration was less than one minute.…”
mentioning
confidence: 99%
“…In our study, the patient uploader rate was only 31%. In contrast, the patient uploader rate was 59.2% for the methotrexate self-injection education article and was 79.6% for the self-administer subcutaneous anti-TNF agent injections article [12, 16]. We assume that such a difference could have occurred since methotrexate and subcutaneous anti-TNF are self-administered procedures applied by patients themselves and probably they want to share their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that the reliability of the videos uploaded by health channels and health workers was higher than that of the videos uploaded by patients (72.7% and 62.5%, respectively) [12, 16]. In contrast, Fischer et al [25] observed in a study on videos uploaded only by healthcare workers that the quality and reliable video content rate was 61.5%.…”
Section: Discussionmentioning
confidence: 99%